2014
DOI: 10.1016/j.biomaterials.2013.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Nerve regeneration and elastin formation within poly(glycerol sebacate)-based synthetic arterial grafts one-year post-implantation in a rat model

Abstract: The objective of this study was to evaluate the long term performance of cell-free vascular grafts made from a fast-degrading elastic polymer. We fabricated small arterial grafts from microporous tubes of poly(glycerol sebacate) (PGS) reinforced with polycaprolactone (PCL) nanofibers on the outer surface. Grafts were interpositioned in rat abdominal aortas and characterized at 1 year post-implant. Grafts remodeled into “neoarteries” (regenerated arteries) with similar gross appearance to native rat aortas. Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 50 publications
(38 reference statements)
0
77
0
Order By: Relevance
“…It will help the scaffold retain its integrity for use in a mechanically dynamic environment upon implantation. 7, 33 To examine the elasticity and ability to recover from reversible deformations, cyclic loading mechanical (hysteresis) tests were performed on dog-bone samples of the PGS control, PGS-TA 15 , and PGS-TA 25 elastomers (Fig. 4A and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will help the scaffold retain its integrity for use in a mechanically dynamic environment upon implantation. 7, 33 To examine the elasticity and ability to recover from reversible deformations, cyclic loading mechanical (hysteresis) tests were performed on dog-bone samples of the PGS control, PGS-TA 15 , and PGS-TA 25 elastomers (Fig. 4A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…35 We made the scaffolds by curing at 150 °C for 24 h because this condition has been established to make PGS vascular graft in our lab. 7, 33 75–150 μm NaCl salt was used as the template to give a nearly identical porous structure and pore size of both scaffolds (Fig. 6C, D).…”
Section: Resultsmentioning
confidence: 99%
“…[35,37,38] Comparing to other widely used synthetic polymers such as poly(lactic acid)(PLA) and poly(lactic-co-glycolic acid)(PLGA)-based materials, PGS triggered lower inflammatory responses and minimal fibrous encapsulation. [35][36][37] As a consequence, PGS-based scaffolds are explored for various soft tissue engineering applications, including vascular graft [39][40][41], nerve guide [42], cardiac patch [43], cartilage tissue [44], and retinal transplantation [45]. In addition, it has been reported that PGS supported phenotypes of osteoblasts in vitro and was a promising osteoconductive substrate for bone tissue engineering application.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to both rapidly degrading graft material and increased porosity the authors demonstrated that: cell adhesion was timely, graft material was safe for implantation without leakage or rupture, and the remodeling process occurred at a rapid rate, resulting in a robust and compliant neo-artery (with intact three-layered vessel architecture). In terms of long-term results in rodents, the same group has demonstrated that, at one year post-implant, the cell-free approach maintained gross appearance similar to native aorta, which similar tissue architecture and response to vasoactive substances as native arteries [33]. This newer, cell-free approach, coupled with the easy handling characteristics of these grafts, has challenged prior conventional thinking regarding the remodeling process -that it should be ''slow'' and hence grafts should be designed to be somewhat resistant to remodeling in the immediate post-implantation period [32,33].…”
Section: Tevg Methodsmentioning
confidence: 91%